2012
DOI: 10.1177/0733464812463430
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Older Adults’ Internet Use for Health Information

Abstract: Technological advancement benefits Internet users with the convenience of social connection and information search. This study aimed at investigating the predictors of Internet use to search for online health information among Chinese older adults. The Technology Acceptance Model (TAM) was applied to examine the predictiveness of perceived ease of use, perceived usefulness, and attitudes toward Internet use on behavioral intention to search for health information online. Ninety-eight Chinese older adults were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 61 publications
2
91
1
1
Order By: Relevance
“…Furthermore, Lee & Chang [35] revealed that PEOU is significantly correlated with attitude or intention through PU. Wong et al [36] also indicated that PEOU is positively correlated with behavioral intention to use the Internet for health-related Information. Yun and Park [37] explored that attitude towards using the Internet for pursuing disease information had a positive influence on the intention to use this technology for pursuing disease information.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Furthermore, Lee & Chang [35] revealed that PEOU is significantly correlated with attitude or intention through PU. Wong et al [36] also indicated that PEOU is positively correlated with behavioral intention to use the Internet for health-related Information. Yun and Park [37] explored that attitude towards using the Internet for pursuing disease information had a positive influence on the intention to use this technology for pursuing disease information.…”
Section: Research Hypothesismentioning
confidence: 99%
“…The quality of the information provided on health sites is critical. [15] When the ideas of the patients about the information they gathered from internet sources were investigated, 31% of them reported that this information was impressive, 27% of them said they found it confusing, and 76% reported that it was contradictory. When they were asked about the reliability of the information, 60.7% of them responded that it was partially reliable, 23.9% said it was reliable, and 4.3% of them replied that it was not credible.…”
Section: Discussionmentioning
confidence: 99%
“…The internet could be used for health education if users are directed to reliable sources [60]. The internet provides anonymised information and facilitates privacy and control over the information sought, which is important to many men [61,62].…”
Section: Principal Findingsmentioning
confidence: 99%